East Indian Priest, Trinidad, B.W.I. - No. 48 - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2008)
East Indian man, dressed in a loin cloth, blowing a conch shell.
Colour: Brown and White; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Hindu priests--Trinidad and Tobago; Trinidad and Tobago; Men--Trinidad and Tobago; Ethnic costume--Trinidad and Tobago